Implicit learning in children with Childhood Apraxia of Speech. (March 2022) - Bombonato, Clara; Casalini, Claudia; Pecini, Chiara; Angelucci, Giulia; Vicari, Stefano; Podda, Irina; Cipriani, Paola; Chilosi, Anna M.; Menghini, Deny
Highlights: Assessment of implicit memory in children with Childhood Apraxia of Speech. Evaluation of reaction times in a task where motor precision or verbal processing is not required. Non-verbal difficulties in children with Childhood Apraxia of Speech. Abstract: Background: Childhood Apraxia of Speech is a severe and persistent clinical subtype of Speech Sound Disorder. Given the difficulties in the acquisition, programming and control of the movements underlying speech and the slowdown in a wide range of non-linguistic skills, the difficulty in implicit learning of sequential information could play a role in the disorder, contributing to understand its etiopathological mechanisms and behavioral manifestations. Aims: The present study was aimed at investigating implicit learning in children with Childhood Apraxia of Speech. Methods and procedures: Twenty-five children with Childhood Apraxia of Speech, aged between 4 and 12 years, were matched for IQ and age to a control group of 25 typically developing children. Implicit learning of participants was assessed by Serial Reaction Time Task. Outcome and results: Children with Childhood Apraxia of Speech did not show implicit learning, as documented by the absence of differences between reaction times in the sequenced block and the random block, usually considered as a measure of implicit learning effect. Conclusion and implications: Our results underline an implicit learning deficit in children with Childhood Apraxia of Speech, supporting the concept of a disorder not only confined to the speech domain, but also involving non-linguistic skills, in a composite and complex picture.